RELEASE OF NEW HIGH YIELDING MUNGBEAN VARIETY BAHAWALPUR-MUNG-17; SUITABLE FOR PUNJAB ESPECIALLY IN SOUTHERN PUNJAB (PAKISTAN) - KHAN, MF; KHAN, LF; YOUSAF, MW; ASIM, MM; UZAIR, M (Biological and Clinical Sciences Research Journal, 2024)
Bahawalpur-Mung-17 was developed through a cross between VC-3726 an exotic line received from AVRDC, Thailand, and NM-36 which was a locally advanced line with the bold grain. Bahawalpur-Mung-17 was tested in a series of experiments for production technology and yield performance at the Regional Agricultural Research Institute, Bahawalpur and farmers’ fields in Yazman, Rahim Yar Khan, Hasilpur, Bahawalpur with average yield of 1465 Kg ha-1 coupled with N:P: K dose at the rate of 23:34:25 Kg/ha gave maximum yield when planted in row-to-row distance of 45cm apart. Bahawalpur-Mung-17 yielded among all candidate lines included in the National Uniform Yield Trial (NUYT)-2013 and 2014 with an average yield of 1020 and 1028 Kg ha-1 respectively at 15 locations across the country, with the highest grain yield of 1380 Kg ha-1 at AZRI-Bahawalpur during 2013 and 2475 Kg/ha at NIAB-FSD. Bahawalpur-Mung-17 outclassed, among 18 candidate lines in 2013 and 14 candidate lines in 2014 across the country, and stood on top of the victory stand. Punjab Seed Council approved it for general cultivation in Punjab. Bahawalpur-Mung-17 gave 26 % more yield than check NM-2011 in 2013 and has 8.43 % more yield and potential than best check AZRI MUNG-2006 and NM-2011 and showed moderately resistant to disease Mungbean Yellow Mosaic Virus (MYMV) at maturity, morphologically different from existing mung bean varieties (light green) and drought resistant.